Time for metrics in emergency surgical care – the role of an emergency surgery registry (Anestezjologia Intensywna Terapia, 2019)
There is abundant local, national, and international evidence that clinical decision-making in emergency general surgery (EGS) is frequently sub-optimal, and this has a negative impact on the quality and safety of care and patient outcomes. The barriers to achieving high-quality, safe, and effective EGS care across health systems are manifold and multifactorial. It is suggested that emergency surgery registries may provide a suitable foundation to enable interventions that lead to improvements in quality in this area. Data from surgical registries may serve multiple purposes, including improving the quality of healthcare and the enhancement of patient safety. The increasing sophistication and analytic capabilities of clinical registries and databases contribute considerably in all of these domains due to their use of accurate, credible, risk-adjusted, and concurrent clinical data, which are acquired for these specific purposes. The emergency surgery outcomes advancement (eSOAP) project commenced during late 2018, with the aim of establishing the feasibility of prospective data capture on all EGS admissions and assessing the outcomes and impact of clinical pathways for patients admitted to EGS services in Letterkenny University Hospital (Republic of Ireland), Altnagelvin Hospital (Northern Ireland), and Raigmore Hospital (Scotland). eSOAP seeks to address deficits in EGS care by enabling an assessment of patient outcomes, enhancing the quality and safety of patient care, and providing an effective template for EGS registry development. It will achieve this through the provision of meticulous, valid, risk-adjusted, and concurrent clinical data. The comprehensive information within the eSOAP registry will promote transparency in respect of the functioning of individual surgical teams and services and increase understanding of the complex systems involved in the delivery of EGS care.